EP525 The role of LVSI to define the best adjuvant treatment in endometrial cancer (EC). (1st November 2019) - Mirri, F; Fuso, L; Ferrero, A; Ribotta, M; Volpi, E; Macchi, C; Parpinel, G; Badellino, E; Laudani, ME; Potenza, E; Zola, P
Abstract : Introduction/Background: Endometrial cancer is the fourth neoplasia in the female population with 88 000 new cases annually in Europe. Recently great efforts have been made to modulate treatments based on the risk of relapse. One of the risk factors included in ESGO guidelines is lymphovascular space invasion (LVSI). In patients LR (IA G1), LVSI determines whether to add EBRT when the lymph node status is unknown. In HR group (IAG3-IBG1-2) LVSI is useful to decide if adding EBRT to the BRT or performing just the follow up. Methodology: To verify the role of the LVSI in the management of EC, data from 697 patients treated consecutively were collected from hospital databases (01/2011 to 10/2018) in 3 Centres of the Cancer Network of Piemonte and Valle d'Aosta. Results: LVSI was found in 285 out of 697 tumours collected (40.9%). Stratifying positive LVSI by centre, we found that 12.3% in centre A, 31.7% in centre B, and 5.5% in centre C were positive in LR EC (286 patients G1-2, IA). 43.3% in centre A, 62.5% in centre B, 10.8% in centre C were positive in HR EC (196 patients IA, G3; IB, G1-G2). In order to analyse these differences within centres, we evaluated the determinants of LVSI with mono and multivariate logistic regression analyses. The factors identified related to LVSI are: risk class LR (OR=2.9) vs HR (OR=7.5 p=0.0001); Type I vs II EC (OR=3.3 p=0.001); surgical approach: LPS without manipulation vs LPS with manipulation (OR=2.1) vs LPT (OR=3.1 p=0.001); number of lymph nodes removed during surgery (<20 vs ≥20 lymph nodes; OR 1.8 p=0.01). Conclusion: LVSI, a key factor for the decision of adjuvant treatment, depends on different factors that should be considered in quality control studies. Disclosure: Prof. Paolo Zola has received grants from Astrazeneca, Roche, Pharmamar and Tesaro.